Concerns of corrosive effects with respect to lightning protection systems - Ghavamian, Aidin; Maghami, Mohammad Reza; Dehghan, Shayan; Gomes, Chandima (Elsevier, 2015)
Lightning protection system elements need to be selected from materials which are resistant to corrosion and should be protected from fast degradation. However, over the time corrosion will take place in the presence of galvanically dissimilar metals in the same electrolyte (moisture). Historically, copper, aluminium and copper alloys (including bronze and brass) have been used in lightning protection applications as these materials are highly conductive and abundantly available. Corrosive effects on system components are influenced by the environmental factors such as moisture, soil type and temperature that make the corrosion process highly complex in soil. As per many standards on the installation of lightning protection systems, combinations of materials that naturally form electrolytic couples shall not be used, for example copper and steel, especially in the presence of moisture, in which corrosion will be accelerated. Similarly, the conditions within soil will have adverse effects on the ground system elements. Down conductors entering corrosive soil must be protected against corrosion by a protective covering. The paper presents the causes of corrosion and recent developments in minimising the corrosion associated with lightning protection and grounding systems.